Effects of dietary fibers or probiotics on functional constipation symptoms and roles of gut microbiota: a double-blinded randomized placebo trial. (31st December 2023) - Lai, Hao; Li, Yunfeng; He, Yafang; Chen, Fangyao; Mi, Baibing; Li, Junqi; Xie, Jiawen; Ma, Guoqing; Yang, Jinzhao; Xu, Kun; Liao, Xia; Yin, Yan; et al.
ABSTRACT: Dietary fibers/probiotics may relieve constipation via optimizing gut microbiome, yet with limited trial-based evidences. We aimed to evaluate the effects of formulas with dietary fibers or probiotics on functional constipation symptoms, and to identify modulations of gut microbiota of relevance. We conducted a 4-week double-blinded randomized placebo-controlled trial in 250 adults with functional constipation. Intervention: A: polydextrose; B: psyllium husk; C: wheat bran + psyllium husk; D: Bifidobacterium animalis subsp. lactis HN019 + Lacticaseibacillus rhamnosus HN001; Placebo: maltodextrin. Oligosaccharides were also included in group A to D. 16S rRNA sequencing was used to assess the gut microbiota at weeks 0, 2, and 4. A total of 242 participants completed the study. No time-by-group effect was observed for bowel movement frequency (BMF), Bristol stool scale score (BSS), and degree of defecation straining (DDS), while BSS showed mean increases of 0.95–1.05 in group A to D (all P < 0.05), but not significantly changed in placebo ( P = 0.170), and 4-week change of BSS showed similarly superior effects of the interventions as compared placebo. Group D showed a marginal reduction in plasma 5-hydroxytryptamine. Group A resulted in a higher Bifidobacterium abundance than placebo at week 2 and 4. Fourteen genera showed intervention-specific increasing or decreasing trends continuously, among which Anaerostipes showed increasing trends in groups B and C, associated with BMF increase. Random forest models identified specific baseline microbial genera panels predicting intervention responders. In conclusion, we found that the dietary fibers or probiotics may relieve hard stool, with intervention-specific changes in gut microbiota relevant to constipation relief. Baseline gut microbiota may predispose the intervention responsiveness. ClincialTrials.gov number, NCT04667884. Plain Language Summary: What is the context? Supplementation of dietary fibers, such as psyllium husk or wheat bran (10 15 g/day) may relieve constipation symptoms, but bloating and flatulence are major concerns on a high fiber intake. Functional constipation patients had alternated gut microbiota profiles, while meta-analysis suggested that multispecies probiotics may increase bowel movement frequency and relieve hard stool in functional constipation. Dietary fibers or probiotics may lead to before-after changes of gut microbiota in patients with functional constipation, but time-series continued changes of gut microbiota during the intervention are unknown. Elevation of 5-hydroxytryptamine synthesis in enterochromaffin cells may affect bowel movement. And the elevated plasma 5-hydroxytryptamine was observed in functional constipation patients. What is new? Daily supplement of three prebiotic formulas with dietary fibers (polydextrose, psyllium husk, wheat bran, together with oligosaccharides), or a probiotic formula with Bifidobacterium animalis subsp. lactis HN019 + Lacticaseibacillus rhamnosus HN001 effectively relieved hard stool in functional constipation patients after 4 weeks intervention. We identified continued increasing or decreasing gut microbial genera over the intervention. Dietary fiber – gut microbiota ( Anaerostipes )—constipation relieve (bowel movement frequency) evidence axis was identified in this human trial. Probiotic supplementation marginally reduced plasma 5-hydroxytryptamine, possibly associated with changes in BMF-related gut microbial genera. Intervention-specific baseline gut microbiota well predicted the responsiveness of constipation symptom relief. What is the impact? We provided references for the dosage and duration of dietary fiber/probiotics recommendations for adults with functional constipation, and advanced the microbial genera evidences of the fibers/probiotics-microbiota-laxation theory in humans. Graphical abstract: uf0001